A revista e a propaganda: o projeto político-cultural do Estado Novo nas páginas da Ilustração Brasileira - Silva, Geanne Paula de Oliveira (2011)
Taking the magazine Ilustracao Brasileira, especiallu the 104 first editions of its third phase of publications may 1935 to january 1944 as the source and, at the same time, as a privileged object of research, this study has as main aim to examine the political propaganda of the Brazilian Estado Novo conveyed in the pages of this magazine. By focusing this propaganda content, the magazine Ilustracao Brasileira is presented as a research resource, as traces that make possible the construction of knowledge about the historical period known as the Estado Novo in Brazil s history. As the magazine is taken as part of research, it also becomes the object of research. From this perspective, I examine the content of political propaganda text and images trying to show how the estado-novista s political cultural project appeared itself formatted in the pages of Ilustração Brasileira. At the same time, I take the magazine itself as an object of study its history, project(s) chart(s), materiality in an attempt to show the place occupied by that publication in the history of the brazilian illustrated press and within the Estado Novo s political-cultural project.